2022
DOI: 10.3389/fcimb.2022.881071
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between the Gut and Brain: Importance of the Fecal Microbiota in Patient With Brain Tumors

Abstract: BackgroundVariations in the gut microbiota may affect the metabolism, inflammation and immune response of the host. Microbiota dysbiosis has been extensively investigated in neurological disorders and diseases of the central nervous system (CNS). However, the alterations of the gut microbiota in patients suffering from brain tumors and the associations of the gut microbiota with these diseases remain unknown. Herein, we investigate the alterations of the gut microbiota community in patients with brain tumors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…Estimated effects between infection and CNS tumors in our study were moderate in size and our results suggested that viral and enteric infections showed a stronger positive association than overall infections. This finding coincides with the emerging model on the gut‐brain axis and its contribution to brain tumors 50,51 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Estimated effects between infection and CNS tumors in our study were moderate in size and our results suggested that viral and enteric infections showed a stronger positive association than overall infections. This finding coincides with the emerging model on the gut‐brain axis and its contribution to brain tumors 50,51 …”
Section: Discussionsupporting
confidence: 90%
“…This finding coincides with the emerging model on the gut-brain axis and its contribution to brain tumors. 50,51 Our results showed that germ cell tumor cases were more likely to have been diagnosed with infections than controls, particularly appendicitis. 20 Mumps is rare in the Denmark population due to high vaccination rates.…”
Section: Discussionmentioning
confidence: 67%
“…Current evidence suggests that the gut harbors a multitude of microbes that produce various small molecules impacting crucial pathways associated with immune balance and neurological homeostasis, particularly within the gut-brain axis [31] . In recent years, a growing body of evidence has emphasized the pivotal role of gut microbiota and its metabolic products in various neurological conditions and diverse brain tumors [18,19] . Understanding the intricacies of gut microbiota characteristics and regulation is increasingly crucial for diagnosing and treating individuals with different brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of the brain-gut axis [17] has sparked increased research into the relationship between gut microbiota and various nervous system diseases, including Alzheimer's disease [7] and different types of cerebral tumors [18,19] . Meanwhile, emerging evidence suggests strong connections between gut microbiota and different types of pituitary adenomas.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CNS can regulate intestinal functions through some neuropeptides such as 5-HT, γ-aminobutyric acid, norepinephrine and dopamine, etc. Numerous studies have confirmed that excessive or harmful chronic psychological stress can cause intestinal dysfunction, increased mucosal permeability, gut dysbiosis, microbial imbalance and bacterial translocation ( Rhee et al., 2009 ; Stasi et al., 2012 ; Forsythe et al., 2016 ; Sundman et al., 2017 ; Martin et al., 2018 ; Dalton et al., 2019 ; Jacobs and Mayer, 2019 ; Deng et al., 2021 ; Li et al., 2022 ). It indicates the intersection of the brain-gut axis and gut-liver axis is intestinal bacterial translocation ( Chudzik et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%